Implementation of Online Donation Information System: Implementasi Sistem Informasi Donasi Online - Nurul Ardhilah; Firdha Aprilyani (Universitas Singaperbangsa Karawang, 2021)
The Hubbu Ahmad Center Foundation is a foundation that focuses on socio-religious activities, helpsmeet the needs of orphans and poor people, and is active in moderate Islamic da'wah activities. TheHubbu Ahmad Center Foundation has carried out various activities including, through donations fromgenerous people but for now the donation system that is running is still using methods such as usingmedia pamphlets as its promotion and Microsoft Excel as its record, therefore there is a need for asystem to manage it so that can be well recorded. The purpose of this research is to create a web-basedonline donation information system that can later be systemized properly using the MySQL database,namely PHPMyadmin, and using structured modeling with UML (Unified Modeling Language) whichuses the Prototype method in it. The final result or system resulting from this research is to be able tobuild a well-database online donation system.